1996
DOI: 10.1088/0022-3727/29/1/025
|View full text |Cite
|
Sign up to set email alerts
|

A fast ion conducting mixed glass system: x[0.75AgI:0.25AgCl]: (1 - x)[]. Transport property and battery discharge characteristic studies

Abstract: Ionic transport properties and battery discharge studies on the fast ion conducting quenched mixed glass system x[0.75AgI:0.25AgCl]: (1 - x)[] are reported, where in molar wt %. The conventional host AgI has been replaced by an alternative compound: `a quenched [0.75AgI:0.25AgCl] mixed system'. The compositional ratio, for x = 0.75, exhibited the optimum conductivity, at C. Samples of the optimum conducting composition were prepared from the melt at two different cooling rates, namely about and about , ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
7
12
0
Order By: Relevance
“…5. The rapid increase (decrease) in 'n' (It) with increasing temperature is akin to those reported earlier [10,11,13] and can be explained in the light of weak electrolyte and cluster bypass models [30,31].…”
Section: Temperature Dependence Of Lonicsupporting
confidence: 73%
See 1 more Smart Citation
“…5. The rapid increase (decrease) in 'n' (It) with increasing temperature is akin to those reported earlier [10,11,13] and can be explained in the light of weak electrolyte and cluster bypass models [30,31].…”
Section: Temperature Dependence Of Lonicsupporting
confidence: 73%
“…The new host, investigated in the present laboratory, exhibits transport characteristics identical to AgI [8,9]. However, it has been observed that the new host yielded glass/composite electrolytes exhibiting ionic parameters superior to those prepared using AgI [10][11][12][13][14][15][16][17][18]. The present system is an another addition to the series.…”
Section: Introductionmentioning
confidence: 95%
“…This phenomenon is usually observed in a glass electrolyte/composite system. In the logσT -x plot (figure 1), this mixed composite system looks qualitatively similar to those reported in the literature (Magistris et al 1976), but the σ values differ quantitatively at different temperature ranges (Agrawal and Kumar 1996).…”
Section: Compositional Variation In Conductivitysupporting
confidence: 87%
“…The small jump in the conductivity was due to the β -α like transition of the system of fractional amounts of the unstabilized/unreacted host present in the system. The drop in conductivity was probably due to softening of the materials (Agrawal and Kumar 1996). The log σT values of all the mixed composite systems are also intermediate between the host, Cu 2 HgI 4 (Kumari and Secco 1985).…”
Section: Temperature Variations In Conductivitymentioning
confidence: 95%
“…Ag § ions in AgI) is Using the '~t' data obtained as above and '~' data from conductivity measurements, one can easily evaluate 'n' at various temperatures for purely ionic systems. In fact, this experimental procedure has been employed by us for the measurements of '~t' and 'n' in the number of Ag § ion conducting ionic/superionic systems [11,[26][27][28][29][30][31].…”
Section: Experimental Aspectsmentioning
confidence: 99%